2019
DOI: 10.1038/s41598-019-49786-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis and implication of Rab1A in gastrointestinal relevant tumor

Abstract: Gastrointestinal cancers have become increasingly prevalent worldwide. Previous studies have reported an oncogenic function of Rab1A in colorectal cancer and hepatocellular carcinomas via the mTOR pathway. However, the exact role of Rab1A in gastrointestinal cancers remains elusive. We detected significantly higher expression of Rab1A in the gastrointestinal tumor tissues compared to that in other cancer types following an in silico analysis of TGCA and GTEX databases. Furthermore, Rab1A was overexpressed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The final staining score was determined by color intensity and positive cell rate, ranging 0–12 which was described in our previous study. 23 , 24 Patients were classified into two groups: scores 0–4 were considered as none or low, while 5–12 were considered as high expression.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final staining score was determined by color intensity and positive cell rate, ranging 0–12 which was described in our previous study. 23 , 24 Patients were classified into two groups: scores 0–4 were considered as none or low, while 5–12 were considered as high expression.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 20 µg protein was then separated by 8% SDS‑PAGE and then transferred onto a PVDF membranes according to methods described previously. 23 , 24 Antibodies against DAB2IP (dilution 1:1000; #ab87811, abcam), cyclin D1 (dilution 1:1000; 26939-1-AP, proteintech), p21 (dilution 1:1000; 10355-1-AP, proteintech), p-AKT (Ser473) (dilution 1:1000; #4058, CST), AKT (dilution 1:1000; #9272, CST), p-ERK (dilution 1:1000; #4370, CST), ERK (dilution 1:1000; #4695, CST) and Tubulin (dilution 1:2000; #AF5012, Beyotime) were used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Rab1A overexpression promotes mTORC1 signaling and oncogenic growth in an amino acid- and mTORC1-dependent manner. Conversely, Rab1A knockdown selectively attenuates the oncogenic growth of Rab1-overexpressing cancer cells ( 55 , 58 ). Thus, we hypothesize that the interaction of PE_PGRS proteins with Rab1A activates Rab1A GTP activity, resulting in mTOR activation and autophagy inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that Rab1A expression was obviously linked to the depth of tumor invasion, lymph node invasion, venous invasion, and TNM staging. Rab1A overexpression is positively correlated with poor prognosis in several gastrointestinal cancers, such as CRC 6 and GC 13 . Consistent with these reports, our findings indicated that lower Rab1A expression indicated better prognosis in patients with CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated Rab1A acted as an oncogene and Rab1A overexpression promoted a worse prognosis in multiple cancer types such as gastric cancer 10 and hepatocellular carcinoma 11 . In addition, Rab1A overexpression has been positively associated with proliferation, migration, and drug-resistance in various cancers 12,13 .…”
mentioning
confidence: 99%